2019
DOI: 10.2147/ott.s210575
|View full text |Cite
|
Sign up to set email alerts
|

<p>PLK1 contributes to autophagy by regulating MYC stabilization in osteosarcoma cells</p>

Abstract: BackgroundPLK1, a typical PLK protein, is the main driver of cancer cell growth and proliferation. It is an inhibitor of the protein kinases that is currently being investigated in clinical studies. It is often used as a tumor marker, as high PLK1 expression correlates with poor prognosis in cancer. Overexpression of MYC is a hallmark of many human cancers. MYC modulates the transcription of thousands of genes that required to coordinate a series of cellular processes, including those essential for growth, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…36 Mo et al found that PLK1 could promote the proliferation of MYC-amplifying OS cells through autophagy. 37 These results are consistent with our research results. It is suggested that miR-1224-5p regulates the effect of PLK1 expression on the occurrence and development in OS.…”
Section: Discussionsupporting
confidence: 93%
“…36 Mo et al found that PLK1 could promote the proliferation of MYC-amplifying OS cells through autophagy. 37 These results are consistent with our research results. It is suggested that miR-1224-5p regulates the effect of PLK1 expression on the occurrence and development in OS.…”
Section: Discussionsupporting
confidence: 93%
“…In 2003, Tsuneoka et al demonstrated that the overexpression of MYC in rat fibroblasts significantly increased the number of autophagic vacuoles [ 44 ]. In a more recent study, it was found that the loss of MYC can reduce autophagy and further restrain cellular proliferation in osteosarcoma cells [ 45 ]. Thus, results from these two studies support the concept that MYC can regulate autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the MYC gene is also reported to be amplified in a subset of OS ( Ladanyi et al, 1993 ). MYC promotes the proliferation of OS cells through the autophagy pathway ( Mo et al, 2019 ). Cross-species genomics identified DLG2 as a tumor suppressor in OS ( Shao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%